2016
DOI: 10.5897/ajmr2016.8318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic and inorganic fertilizer applications on phosphate solubilizing bacteria in the rhizosphere of maize (Zea mays L.)

Abstract: A field experiment was conducted between August and October, 2014 at the Department of Microbiology to assess the effect of organic and inorganic fertilizers on the population and activities of Phosphate Solubilizing Bacteria (PSB) in the rhizosphere of maize variety BR9928DMRSR-Y. Three treatment groups were used in the study and these were: Groups which received applications of organic fertilizer (Poultry litter) alone, groups which received applications of inorganic fertilizer (NPK) and the third group whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Furthermore, the decomposition of organic matter by inoculated decomposers is inseparably linked with the synthesis of new organic compounds and the release of elements (mineralization) that discriminated the inoculated compost from the un-inoculated one and sequentially reflected on biodiversity in rhizobiome. In harmony with our results, Patrick and Adeniyi (2016) showed that soil treated with organic fertilizers enhanced total heterotrophic bacteria and phosphate solubilizers within the rhizosphere of maize plants compared to NPK fertilization due to the decomposition of organic matter, which is important for the proliferation of soil microorganisms in the soil. The stimulative impact of organic fertilizers against mineral fertilizers was lately reviewed by Dincă et al (2022).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the decomposition of organic matter by inoculated decomposers is inseparably linked with the synthesis of new organic compounds and the release of elements (mineralization) that discriminated the inoculated compost from the un-inoculated one and sequentially reflected on biodiversity in rhizobiome. In harmony with our results, Patrick and Adeniyi (2016) showed that soil treated with organic fertilizers enhanced total heterotrophic bacteria and phosphate solubilizers within the rhizosphere of maize plants compared to NPK fertilization due to the decomposition of organic matter, which is important for the proliferation of soil microorganisms in the soil. The stimulative impact of organic fertilizers against mineral fertilizers was lately reviewed by Dincă et al (2022).…”
Section: Discussionsupporting
confidence: 90%
“…In both soils, our findings revealed that the bacterial community population was frequently larger than the fungal community population in all treatments, as previously mentioned by Kamaa et al (2011). It has been demonstrated in previous research that organic and chemical fertilizers help PSB (Richard and Ogunjobi, 2016). In both acidic and charland soils, however, we found that IPNS or chemical fertilizer exerted on influence on PSB.…”
Section: Effect Of Ipns On Microbial Populationsupporting
confidence: 84%
“…More exudates and plant compounds are released as a result of this breakdown product, which the rhizosphere bacteria can utilize. As a result, the bacterial biomass in the rhizosphere has increased (Richard and Ogunjobi, 2016).…”
Section: Effect Of Ipns On Microbial Populationmentioning
confidence: 99%